A Comparative Thermodynamic Analysis of Gas–Solid Sorption System Based On H2–La0.9Ce0.1Ni5/LaNi4.7Al0.3 and NH3–NaBr/MnCl2. (March 2017) - Sharma, Rakesh; Kumar, E. Anil
Abstract: Sorption cooling system based on gas–solid reaction is a newly emerged energy conversion technology which is benign to environment. In this work, sorption cooling system, based on the gas–solid pairs of H2 –La0.9 Ce0.1 Ni5 /LaNi4.7 Al0.3 and NH3 –NaBr/MnCl2 is thermodynamically analyzed using the first and second law of thermodynamics. The COP of H2 – La0.9 Ce0.1 Ni5 /LaNi4.7 Al0.3 and NH3 –NaBr/MnCl2 based sorption system is 0.70 and 0.41 respectively while neglecting mass ratio and 0.23 and 0.33 respectively while considering mass ratio as 4. Also it is observed that the sorption cooling system based on NH3 –NaBr/MnCl2 can produce refrigeration effect below 0 °C while H2 –La0.9 Ce0.1 Ni5 /LaNi4.7 Al0.3 sorption system can be operated at a low temperature of about 130 °C. Irreversibility in H2 –La0.9 Ce0.1 Ni5 /LaNi4.7 Al0.3 sorption system is small in comparison to NH3 –NaBr/MnCl2 based system, due to lower reaction enthalpy values of regenerating material in case of H2 –La0.9 Ce0.1 Ni5 /LaNi4.7 Al0.3 system. The reactor mass contributes significantly in the irreversibility of the system.